Impacts of Climate Change on Adaptation and Mitigation in Pakistan, South Asia: Review Study - Jawad Abdullah Butt; Yasmin Nergis; Mughal Sharif (Journal of Sustainable Environment)
Pakistan is predicted to experience a greater rise in temperature than the global average. The country's southern regions are predicted to see an increase in temperature. It is predicted that the number of hot days and nights will rise dramatically. Predictions for rainfall in Pakistan show no discernible patterns of systematic change. A pattern of rising rainfall in the lower and upper Indus Basins. Rising air and sea temperatures are predicted to produce a considerable rise in the frequency of floods. 33 million people could be affected annually by floods in 2030, and the sea-bed area of South Asia will also be submerged. Studies show that corrective measures for adaptation and mitigation should apply. The national performance assessment based on 14 indicators should follow four categories. One of the world's regions that is most sensitive to the many direct and indirect consequences of climate change is South Asia. These implications include rising sea levels, increased cyclonic activity, altered ambient temperatures, and changed precipitation patterns. The continuous rise in sea level has already flooded many of the low-lying islands in the Sundarbans constituency, forcing thousands of people to evacuate. The assessment of a country's progress toward its Nationally Determined Contributions (NDCs) and 2030 targets.